Exploring Motivators for Students in the Pursuit of Further Studies and Career Development - Alvin Y.T. WONG (Communications of International Proceedings, 2022)
Students’ motivation to pursue career development captured educators’ attention in recent decades.  In spite of the wide discussion on students’ motivation, more studies are needed to further explore factors that motivate students with different academic background for pursuing further studies and career development.   Besides, the growing trend of multiple career path justifies further research in this area for designing career development activities.  This study discussed the impact of a sharing session conducted in a tertiary education institution in 2020.  An alumnus who had similar academic background with participants at the stage of tertiary education entry, and had experienced multiple career path was purposefully invited to share with sub-degree and degree students. It was found that the commonality between the speaker and participants (Jarret and Ellis, 2020) and the pathway thinking (Snyder, 1994) are potential factors that could enhance students’ confidence and motivation for pursuing further studies and career development.
Keywords: Students’ motivations; commonality; pathway thinking; multiple career path